Producers bargaining over a quality standard - Cédric Argenton (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
We study an asymmetric information model in which two firms are active on a market where buyers only observe the average quality supplied. Quantities and cost structures are exogenously given and firms compete in quality. Before choosing their qualities, they bargain over a perfectly enforcable minimum quality standard. The bargaining outcome is given by the Kalai-Smorodinsky (KS) solution. Agreement on a binding standard is possible only if the firms are sufficiently similar with respect to their production costs. The agreed-upon standard always falls short of the joint-profit-maximizing (or, for that matter, the efficient) level. It is decreasing in the high-cost producer's cost of production. Yet, it first increases then decreases with the low-cost producer's cost of production, showing that the latter's bargaining position can be enhanced by seemingly adverse cost changes.
Keywords: D43; D82; L13; L15; 330; asymmetric information; minimum quality standard; duopoly; bargaining; free riding; Verarbeitendes Gewerbe; Produktqualität; Duopol; Verhandlungen; Trittbrettfahrerverhalten; Asymmetrische Information